2018
DOI: 10.1016/j.pmrj.2018.06.007
|View full text |Cite|
|
Sign up to set email alerts
|

Getting the Best Out of Advanced Rehabilitation Technology for the Lower Limbs: Minding Motor Learning Principles

Abstract: Advanced technology, including gait‐training devices, is increasingly being integrated into neurorehabilitation. However, to use gait‐training devices to their optimal potential, it is important that they are applied in accordance with motor learning and locomotor training principles. In this article, we outline the most important principles and explain how advanced gait‐training devices are best used to improve therapy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…This enables training at the patient's optimal threshold while avoiding frequent and therefore time-consuming falls. The alternative option of adding handheld assistive devices to the training is in contradiction with established locomotor training principles [32,97] as well as with emerging principles of reinforcing functional remapping through arm use [10,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables training at the patient's optimal threshold while avoiding frequent and therefore time-consuming falls. The alternative option of adding handheld assistive devices to the training is in contradiction with established locomotor training principles [32,97] as well as with emerging principles of reinforcing functional remapping through arm use [10,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…An elegant solution which does not require reliance on external, arm-based support, would be a stabilizing mode as an integrated feature of the BWS system. Such a feature must be easily scalable to the functional level of the patient to provide a sufficiently large challenge for highly functioning patients, while avoiding overly challenging conditions for less functioning patients [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…3 In recent years, robotic devices have been proposed as tools to complement traditional therapy by means of novel rehabilitation programs, based on robot-mediated repeatable, intense, and motivating exercises, integrated with an enriched virtual environment that can feature improvements in movement quality. 11,12 Among all, Robot-Assisted Gait Training (RAGT) approaches have found relatively high success for the treatment of subjects with balance and gait dysfunctions. Two main design and control approaches can be undertaken to implement robot-mediated physical therapy, exoskeletal-or endeffector-based mechanisms.…”
Section: What Is the Impact Of Robotic Rehabilitation On Balance And ...mentioning
confidence: 99%
“…Robot-assisted gait training (RAGT) is a promising technique for rehabilitation after neurological disorders such as stroke or spinal cord injury (SCI). RAGT can be used to provide intensive, repetitive and task-specific training, while it also contributes to reduce physical load for therapists [1]. Reviews of previous studies have shown that RAGT can increase the likelihood that people walk independently after stroke, and that it is most effective in the acute phase after stroke/SCI and in the most impaired patients [2,3].…”
Section: Introductionmentioning
confidence: 99%